1992
DOI: 10.1515/rnam.1992.7.5.405
|View full text |Cite
|
Sign up to set email alerts
|

Semianalytical version of approximation of system of equations in the ‘b-ε’ turbulence model

Abstract: A model is developed, and a difference scheme is constructed for obtaining the vertical turbulence coefficient. The scheme is based on a mathematical analysis of the 'b-δ' turbulence model and a suitable choice of input parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…The Tke evolution (figure 9) of the present experiment compares much better with the observations, Stull (1988) and the comparison seen in this experiment is as good as it is in the earlier experiment. As noted by Kochergin and Sklyar (1992), the smaller the differences C4 -C3, the smaller the Tke values. Thus in the last two experiments we note that the Tke evolution agrees with observations (Stull 1988), if the constants chosen are those we have arrived at, namely Ca = 3/2 and C 3 = 4/3 as well as with those proposed by Marchuk et al (1977).…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…The Tke evolution (figure 9) of the present experiment compares much better with the observations, Stull (1988) and the comparison seen in this experiment is as good as it is in the earlier experiment. As noted by Kochergin and Sklyar (1992), the smaller the differences C4 -C3, the smaller the Tke values. Thus in the last two experiments we note that the Tke evolution agrees with observations (Stull 1988), if the constants chosen are those we have arrived at, namely Ca = 3/2 and C 3 = 4/3 as well as with those proposed by Marchuk et al (1977).…”
Section: Methodsmentioning
confidence: 85%
“…However the solution of problems ( 34) and ( 35) can tend to zero or to infinity depending on parameters C 3, C 4 and F (Kochergin and Sklyar 1992). Particularly, they have shown that in case F > 0, the solution tends to zero when C 4 < C a and tends to infinity when C 4 > C 3.…”
Section: Analytical Discussionmentioning
confidence: 99%